Anthropometric Study of Correlation between the Selected Craniofacial Measurements with the Stature in Adult Bangladeshi Manipuri Males (Mugda Medical College Journal, 2024)
Cephalofacial anthropometry can be useful for racial identification, forensic scientist, physical anthropologist, genetic counsellors as well as reconstructive surgery for the purposes of identification of an individuals and understanding human physical variation, gender and ethnicity especially with facial recognition as a tool in recent advances in biometrics. Stature is one of the important criteria for personal identification which has a proportional biological relationship with every parts of the human body like head, face, trunk, extremities and vertebral column. In this study, our main goal is find out the correlation between the selected craniofacial measurements with the stature in Adult Bangladeshi Manipuri males. This cross-sectional study was carried out in 100 healthy adult males from March 2017 to February 2018 in the Department of Anatomy, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh. Descriptive statistics and testing of hypotheses were used for the analysis using SPSS software (version 22.0). Here non- significant positive correlations of the stature with the mandible height and significant positive correlations of the stature with mandible breadth was found. The Mean (±SD) of Mandible height (sto-gn) was 4.44 (±0.69), Mandible breadth (go-go) was 11.45 (±0.57). This study will be anticipated to provide baseline quantitative data on the linear craniofacial measurements and the stature of adult Bangladeshi Manipuri males. And using larger samples with non-contact measurement technique will help in defining craniofacial anthropometric profiling of the adult Bangladeshi Manipuri males.Mugda Med Coll J. 2024; 7(1): 19-25